Morphological Analysis on Affixes Found in Song Lyrics Composed by Taylor Swift - Manalu, Sri Hartati Nelvi; Purba, Resperdiana (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to analyze the types of affixes found in Taylor Swift's song lyrics in the album "Folklore". The method used in this research is descriptive qualitative with data collection techniques through documentation. The data collection process involved five steps: downloading, reading, underlining, classifying, and coding. The results showed that out of 469 data, 464 data (98%) were found to be inflectional affixes. The details are -s/es as much as 188 data (40%), -ing suffix as much as 103 data (21%), -ed suffix as much as 97 data (20%), -en suffix as much as 32 data (6%), -'s suffix as much as 25 data (5%), -est suffix as much as 15 data (3%), and -er suffix as much as 4 data (0.8%). A total of 5 data (1%) are derivative affixes which only consist of the suffix -less. This research provides a deeper understanding of the use of affixes in song lyrics, and shows the flexibility and richness of the English language through morphological processes.